Clinical and Morphological Evaluation of Meibomian Glands in Dry Eye Disease - Shrestha, Poonam; Subba, Kishore (Journal of Institute of Medicine Nepal, 2025)
Introduction Studies on Meibomian gland morphology and association with dry eyes are not common in our scenario. The objective of this study was to know the clinical pattern and morphology of Meibomian glands and its association with dry eyes. Methods This was prospective observational study done in Cornea clinic of Nepal Eye Hospital, Kathmandu, Nepal for a period of one year (December 2022 through December 2023). All the patients aged ≥20 years who were diagnosed with Dry eye disease was included in the study. The study variables included age, sex, Ocular surface disease index (OSDI), Schirmer test, Tear break up time (TBUT), Lissamine staining, Meibomian gland loss, Meibomian secretion and dry eyes severity. Descriptive analysis of data was done using frequencies and percentage and correlation between parameters were done using Pearson's test. Results Out of fifty cases of dry eye diseases, there were 24 (48%) male and 26 (52%) female with mean age 46.47 years (SD ± 11.96). Most of the patients presented with grade 2 severity of dry eyes (44%, n=22) and the Meibomian gland loss was mainly grade 3 type (60%, n=30). There was a strong positive correlation (r = 0.621, p < 0.01) between Meibomian gland loss and OSDI Score, also strong positive correlation (r= 0.584, p < .001) Meibomian gland secretion and dry eye severity. Conclusion The severity of dry eye is positively correlated with Meibomian gland loss and the meibum quality.